2019
DOI: 10.1177/0269215518803144
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability and limits of agreement of the Six-Spot Step Test in people with Parkinson’s disease

Abstract: completed again. The agreement was estimated by Bland-Altman statistics with 95% limits of agreement, and reliability was estimated by the intraclass correlation coefficient. Results: Subjects had a mean (SD) age of 67.8 (6.8) years, a median (range) Hoehn and Yahr score of 2.5 (1-4) and a mean (SD) Six-Spot Step Test score of 8.1 (1.8), 7.6 (1.7) and 7.6 (1.6) seconds on test occasions 1 to 3. An agreement for within-day and day-today of ±1.8 (±23.7%) and ±2.2 (±26.7%) seconds was found, respectively. The rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
(35 reference statements)
2
14
0
Order By: Relevance
“…The Six-Spot Step Test shows promising concurrent validity to other recommended clinical tests for encompassing balance capacity and functional mobility making it a reasonable and easily administered alternative to existing assessment scales and clinical tests. Furthermore, using the Six-Spot Step Test in clinical practice, one should expect a reliable assessment tool with an absolute measurement error of approximately two seconds or 25%, 3 as is also reported for related outcomes. 25…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Six-Spot Step Test shows promising concurrent validity to other recommended clinical tests for encompassing balance capacity and functional mobility making it a reasonable and easily administered alternative to existing assessment scales and clinical tests. Furthermore, using the Six-Spot Step Test in clinical practice, one should expect a reliable assessment tool with an absolute measurement error of approximately two seconds or 25%, 3 as is also reported for related outcomes. 25…”
Section: Discussionmentioning
confidence: 99%
“…The Six-Spot Step Test was performed as described by Nieuwenhuis et al 4 (see Supplemental Figure 1), and it has been described in detail in a previous paper from our research group. 3 Importantly, before the start, all participants were verbally instructed and shown by the examiner how to perform the test. Hereafter, all participants completed one Six-Spot Step Test to avoid a potential learning effect between trials as has previously been shown to exist.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations